2020
DOI: 10.1042/bcj20200235
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a naturally occurring mutation V368M in the human glucagon receptor and its association with metabolic disorders

Abstract: Glucagon is a peptide hormone secreted by islet α cells. It plays crucial roles in glucose homeostasis and metabolism by activating its cognate glucagon receptor (GCGR). A naturally occurring deleterious mutation V368M in the human GCGR leads to reduced ligand binding and down-regulation of glucagon signaling. To examine the association between this mutation and metabolic disorders, a knock-in mouse model bearing homozygous V369M substitution (equivalent to human V368M) in GCGR was made using CRISPR-Cas9 techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…V368M (c.1102G > A, p.V368M), a naturally occurring GCGR single nucleotide polymorphism (SNP), was identified as a mild deleterious mutation leading to reduced ligand binding and down-regulation of glucagon signaling. Our previous studies confirmed that mice bearing homozygous V369M (c.1105G > A, p.V369M) substitution in the GCGR ( Gcgr V369M+/+ ) display lower fasting blood glucose levels with improved glucose tolerance, hyperglucagonemia, pancreas enlargement and α-cell hyperplasia [ 22 ].…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…V368M (c.1102G > A, p.V368M), a naturally occurring GCGR single nucleotide polymorphism (SNP), was identified as a mild deleterious mutation leading to reduced ligand binding and down-regulation of glucagon signaling. Our previous studies confirmed that mice bearing homozygous V369M (c.1105G > A, p.V369M) substitution in the GCGR ( Gcgr V369M+/+ ) display lower fasting blood glucose levels with improved glucose tolerance, hyperglucagonemia, pancreas enlargement and α-cell hyperplasia [ 22 ].…”
Section: Discussionsupporting
confidence: 68%
“…Generation of Gcgr V369M+/+ mice was described previously [ 22 ]. The genotypes of all the mice were verified by PCR and confirmed by DNA sequencing (Supplementary Figure S1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations